Resilience, not frailty: A qualitative study of the perceptions of older adults towards "frailty". (2nd August 2019) - Pan, Edmund; Bloomfield, Katherine; Boyd, Michal
Abstract: Background: Despite increasing importance placed upon the identification of frailty among the older population, scholarship is limited around the perception of older adults towards the term. This qualitative study aimed to investigate the perceptions of older adults in a New Zealand setting towards the term "frail". Methods: Twelve participants identified as frail based on unrelated comprehensive geriatric assessment were approached and interviewed in their own homes. Interviews were transcribed ad verbatim and analysed by general inductive approach. Results: There was a diverse conceptualisation of frailty among the participants, across physical, cognitive and social dimensions, which differed from professional definitions of frailty. Participants maintained a neutral stance towards the concept of frailty and, however, reject its application to themselves. They also highlight the importance of independence and resilience in the staving off of frailty and the maintenance of quality of life. Conclusion: This study suggests health professionals should shift focus on clinical encounters with the older patient, away from the deficits of frailty and towards independence, resilience and autonomy. Implications for practice: Frail older adults often reject the term frailty when used about themselves, therefore using this term in communication with older adults may have negative consequences.